DNA oligonucleotide-cis-platin binding: Ab initio interpretation of the vibrational spectra - Andrushchenko, Valery; Wieser, Hal; Bouř, Petr (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2007)
The cis-platin binding to the d(CCTGGTCC)*d(GGACCAGG) model DNA octamer was monitored with infrared absorption (IR) and vibrational circular dichroism (VCD) spectroscopies. The spectra were modeled with the aid of density functional computations and a Cartesian coordinate-based transfer of molecular property tensors from smaller DNA fragments. Because of the fragmentation, the tensors could be calculated with a higher precision. Environmental effects, such as the presence of the solvent or the cis-platin ligand, could be included in the modeling. The solvent was modeled by an explicit inclusion of hydrogen-bound water molecules, positions of which were estimated from a molecular dynamics simulation, or by the polarized continuum COSMO model. The B3LYP and BPW91 functionals used for the calculations of the spectral parameters were combined with the relativistic LANL2DZ platinum pseudo-potentials. The simulations reproduced the main IR and VCD DNA spectral features and explained most of the changes observed experimentally upon metal binding. The results confirmed that the influence of the ligand on DNA vibrational properties is quite complex; it originates in the geometry deformation and normal mode coupling pattern changes of the platinated octamer, as well as in local perturbations of the electronic structure and force field of the GC base pairs to which the platinum is bound. Many of the local effects could be accounted for by a point charge used in place of the metal in the GC complex.
Keywords: cisplatina; Cisplatin; Molecular Structure; Antineoplastic Agents; Spectrophotometry, Infrared; molekulární konformace; chemické modely; Magnetic Resonance Spectroscopy; Financing, Organized; Oligonucleotides; Ions; protinádorové látky; financování organizované; Ligands; magnetická rezonanční spektroskopie; spektrofotometrie infračervená; ligandy; Molecular Conformation; DNA; Chemistry, Pharmaceutical; guanidin; oligonukleotidy; Spectrophotometry; spektrofotometrie; fyzikální chemie; ionty; Guanidine; Chemistry, Physical; molekulární struktura; farmaceutická chemie; Models, Chemical